Implementasi Teknik Editing J-Cut & L-Cut pada Produksi Film Dokumenter “Jejak Tradisi Peuyeum Ketan Kabupaten Kuningan” - Grecia Rahel Nadya Napitupulu; Teddy K. Wirakusumah; Aat Ruchiat Nugraha (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
Peuyeum ketan is a traditional culinary heritage of Kuningan Regency that faces preservation challenges due to globalization and changing public preferences. Documentary films provide an effective medium to document, preserve, and promote local cultural heritage. This study aims to produce the documentary film Jejak Tradisi Peuyeum Ketan Kabupaten Kuningan while implementing J-Cut and L-Cut editing techniques to create smooth audiovisual continuity and enhance audience engagement. The production process consisted of three stages: pre-production, production, and post-production. Pre-production included literature review, observation, concept development, scriptwriting, and production planning. The production stage involved video recording, interviews with resource persons, and documentation of the traditional production process of peuyeum ketan. Post-production focused on editing using Wondershare Filmora, emphasizing the application of J-Cut and L-Cut techniques to improve narrative flow, scene transitions, and synchronization between audio and visual elements. The results demonstrate that these editing techniques produce smoother transitions, more dynamic information delivery, and seamless audiovisual continuity, making the documentary more engaging and informative. Consequently, the documentary serves not only as a medium for cultural preservation but also as an effective promotional tool to increase public awareness and appreciation of the culinary heritage of Kuningan Regency.